Team factors and the moderating effect of top management support on product innovation performance: The Malaysian experience - Mat, Norsiah; Jantan, Muhamad; Mat, Norazuwa; Romli, Ruslan (2012)
This study examined the relationships between team factors, namely functional diversity, trust and coordination and the moderating effect of top management support on product innovation performance.A total of 512 team members in various industries within the manufacturing companies in Peninsular Malaysia participated in this study.This figure comprised of 53 participating companies and 120 teams. The results found the difference in impact of independent variables (team factors) on different dependent variables (task-outcomes and psychosocial-outcomes).The R 2 value is higher for psychosocial-outcomes (R 2 =.67) as opposed to task-outcomes (R 2 =.28).Regarding the direct relations between independent variables and dependent variables, only coordination was found to directly relate to both task and psychosocial-outcomes.Affective trust has direct relations with psychosocial-outcomes only but not on task-outcomes. Regarding the indirect relations between the independent and the dependent variables when moderating variable (top management support) was incorporated in the relationships, it was found that top management support act as an independent for psychosocial outcomes, i.e. quasi moderator but not for task-outcomes.Top management support moderates the relationship between functional diversity and coordination on task-outcomes, and affective trust on psychosocial-outcomes.